Dynamic response analysis and optimization of spatial mechanism with wear clearance - Chen, Xiulong; Wang, Ziguo (Mechanics based design of structures and machines, 2025)
This article aims to explore the impact of joint wear clearance on the dynamic response of spatial parallel mechanisms and proposes a dynamic optimization method to mitigate its deteriorating effects. Taking the 2-RPS-SPR spatial parallel mechanism as the research subject, a dynamic model of this mechanism considering the wear clearance of spherical joints is developed. The effect of wear clearance on the dynamic response of the spatial mechanism is analyzed, and the impact of different initial clearance values on the wear depth of the two spherical joints is discussed. Taking the moment of inertia of the moving platform, and the initial clearance distribution at the spherical joint as the design variables, the dynamic optimization model of the spatial mechanism considering the wear clearance is established. The optimization model is solved using the particle swarm optimization. The optimization findings demonstrate a considerable reduction in wear depth and contact force at the joint of the spatial mechanism. Additionally, the maximum displacement errors in the X and γ directions of the moving platform are reduced by 24.61% and 21.56%, respectively. This study provides theoretical support for enhancing the wear clearance effect and improving the dynamic performance of spatial parallel mechanisms.